Enoxaparin Strategy Appears to Reduce Reinfarction Better than Commonly Administered Unfractionated Heparin in ST Elevation Myocardial Infarction - Antman, Elliott (MD Conference Express, 2006)
Treatment with enoxaparin (a low molecular weight heparin) throughout hospitalization (up to 8 days) significantly reduced the risk of death or nonfatal reinfarction, compared to administration of unfractionated heparin (UFH) for 48 hours in patients with ST-elevation myocardial infarction (STEMI) undergoing fibrinolytic therapy, according to findings from the multicenter multinational ExTRACT-TIMI 25 trial lead by the investigators from the Brigham and Women’s Hospital.